Tertiary educated muslim working women's work decision - Muhammad Adidinizar Zia AhmadKusairee; Mohd Safwan Ghazali; Nurul Ashykin Abd Aziz (2014)
This paper tries to study the tertiary educated Muslim working women’s work decision. We use survey questionnaire and snowball sampling to collect information on the tertiary educated Muslim women’s reason for working and not working, job expectation, encouragement or support from reference groups and future work decision. Research findings reveal that the financial reason is the main reason for working among tertiary educated Muslim women’s reason for working among tertiary educated Muslim women who are currently working. Furthermore, the main factor to encourage these women to remain or to enter labour force is getting jobs that meet their expectation in term of salary and position. Therefore, to attain or to encourage women in the labour market, stakeholders must sufficient jobs that are family-friendly such as flexible working arrangement and jobs that meet their expectations in term of salary and position